Acute renal failure during immediate post transplant period due to a pericardial effusion. (December 2015) - Weerakkody, Ranga; Lokuliyana, Pushpa; Sheriff, Mohammed
Abstract Background Pericardial effusions and acute renal failure are common findings in clinical practice. However, acute renal failure resulting from pericardial effusions (without tamponade) is a rare finding. We report the first such case to occur in a transplanted kidney. Case presentation A 20-year-old Sri Lankan male presented with hypertensive crisis in the background of end stage renal failure. He was thoroughly investigated for secondary causes of hypertension to no avail. He was hemodialysed adequately for 6 months, while being worked up for transplantation. He received an ABO matched, living donor transplant. Immediate post-operative period his urine outputs were poor, soon to became anuric by 6 h post-transplant. Elevated liver enzymes and non-specific increase of resistivity indexes (0.84–0.88) at the Doppler scan raised the possibility of venous hypertension. An echocardiogram showed a moderately large pericardial effusion which was tapped, and found to be a transudate. He started producing urine within 6 h, entered polyuric phase by day 3, and by day 7 his creatinine dropped to reference levels. Vasculitis screen, anti nuclear factor, viral screen, and rickettsia serology were negative. Albumin levels on day 2 were 27 g/l and were replaced using human albumin. The exact cause of pericardial effusion is unclear but hypoalbuminemia, drug-induced and idiopathic are possible causes. He has excellent graft function, no recurrences or constrictive pericarditis after 2 years follow. Conclusion We recommend any patient who has delayed graft function and raised central venous pressures to have an echocardiogram to exclude pericardial effusions. The response to pericardiocentesis had been universally good in reported cases.